2023
DOI: 10.3390/cells12081198
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Enters Human Leydig Cells and Affects Testosterone Production In Vitro

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a SARS-like coronavirus, continues to produce mounting infections and fatalities all over the world. Recent data point to SARS-CoV-2 viral infections in the human testis. As low testosterone levels are associated with SARS-CoV-2 viral infections in males and human Leydig cells are the main source of testosterone, we hypothesized that SARS-CoV-2 could infect human Leydig cells and impair their function. We successfully detected SARS-CoV-2 nucleocapsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The high expression level of ACE2 in various testicular cells, including vas deferens cells, spermatogonial cells, stromal cells, and sertoli cells, renders the testes highly susceptible to SARS-CoV-2 infection ( Fu et al., 2020 ; Hikmet et al., 2020 ; Wang and Xu, 2020 ; Qi et al., 2021 ; Ribeiro et al., 2023 ). Several in vitro and in vivo studies demonstrated the susceptibility of testicular cells to SARS-CoV-2 ( Campos et al., 2021 ; Mahé et al., 2023 ; Chen et al., 2023a ; Li et al., 2023b ). Due to the physiological barriers, SARS-CoV-2 could potentially persist in the semen of recovered patients ( Li et al., 2020a ).…”
Section: Long-term Effects Of Covid-19mentioning
confidence: 99%
“…The high expression level of ACE2 in various testicular cells, including vas deferens cells, spermatogonial cells, stromal cells, and sertoli cells, renders the testes highly susceptible to SARS-CoV-2 infection ( Fu et al., 2020 ; Hikmet et al., 2020 ; Wang and Xu, 2020 ; Qi et al., 2021 ; Ribeiro et al., 2023 ). Several in vitro and in vivo studies demonstrated the susceptibility of testicular cells to SARS-CoV-2 ( Campos et al., 2021 ; Mahé et al., 2023 ; Chen et al., 2023a ; Li et al., 2023b ). Due to the physiological barriers, SARS-CoV-2 could potentially persist in the semen of recovered patients ( Li et al., 2020a ).…”
Section: Long-term Effects Of Covid-19mentioning
confidence: 99%
“…In the cohorts of men who fell ill with COVID‐19 during the very first wave where dramatically reduced circulating tT levels had been found 16 and subsequently followed over time, the tT values progressively recovered, although the increase was very slow and eventually not even complete 17,18 . From a pathobiological standpoint it has been demonstrated that SARS‐Cov‐2 can damage Leydig cells, both structurally and functionally, thus justifying a real drop in circulating tT levels 13,19–24 . Thereof, it is possible to speculate that the viral replication could lead to tT decrease, which may result as a marker of unfavorable outcomes.…”
Section: Introductionmentioning
confidence: 99%